Sistem Pakar Metode Case Based Reasoning untuk Mengidentifikasi Penyakit Psoriasis - M Syahputra; Sarjon Defit; S Sumijan (Jurnal Sistim Informasi dan Teknologi, 2021)
Proriasis is a type of chronic disease of the human skin.problem of psoriasis At the end of the day, theis becoming more interesting because the main cause of this disease has not been found, which has only been found while the cause of psoriasis is genetics. Because the cause is not known for sure, this disease is difficult to cure. Although this disease is not contagious and life-threatening to sufferers, it can damage internal organs if not handled properly. This study aims to determine the level of accuracy in identifying psoriasis in humans. There are several types of symptoms that refer to psoriasis. Furthermore, the data is processed manually with themethod Case Based Reasoning and continued by using a-based expert system software website. The processing stage is to use theprocess, which retrieve is a process of finding the similarities between new cases and existing cases in the knowledge base. The results of the data processing are continued with the calculation of the level of accuracy. The result of testing this method is that there are 100% of the 12 test data. Based on the accuracy of the identification results of this system, this study is very precise in the level of identifying the level of accuracy of psoriasis in humans. Expert testing system has been able to identify thedisease psoriasis specific. Through thismethod Case Based Reasoning , the level of accuracy that can be obtained is quite accurate and can help skin and genital specialists in improving accuracy in identifyingdiseases Case Based Reasoning in humans.